Attitudes of sport parents towards children's eating habits - Ozpinar, Saliha; Yucel, Ali Serdar; Korkmaz, Murat; Herguner, Gulten; Yaman, Cetin; Sevil, Umran; Kuyucu, Michael Mihalis (Sielae & Univ Coruna, Fac Filologia, 2024)
Today, parents have assumed important roles in shaping their children's eating habits in social and daily life. Especially the tendency of parents who do sports to transfer their healthy lifestyles to their children has positive effects on children's eating habits. This study examines the attitudes of parents on this issue and the effects of these attitudes on children's eating habits. In line with the aim of the study, the attitudes of parents who do sports towards their children's eating habits were investigated. The rationale of the study is to focus on how parents' attitudes towards nutrition affect their children's eating habits and the contribution of these attitudes to children's general health and sports performance. The findings of the study show that parents' nutrition attitudes are critical for children to develop a healthy lifestyle. This study was conducted between 20232024 and 860 parents and their children participated in the study. The data obtained from the study were collected using a 5-point Likert-type scale form with validity and reliability and analysed with SPSS 22.0 software. Various statistical techniques such as descriptive statistics, reliability analysis, independent sample t-test, ANOVA, factor and regression analyses were used in the study. The findings obtained at the end of the research show that parents' nutritional attitudes have significant effects on children's eating habits. Parents' attitudes towards healthy eating and physical activity positively affect children's eating habits. Children of parents who do sports develop healthier eating habits, are more active and take part in physical activities. The study reveals that parents' nutritional attitudes contribute to children's general health and sports performance.
Actitudes de los padres deportistas ante los hábitos alimentarios de sus hijos
Keywords: parents; children; nutrition; health; sport